2013
DOI: 10.1371/journal.pone.0066035
|View full text |Cite|
|
Sign up to set email alerts
|

Gauging the Threat: The First Population Estimate for White Sharks in South Africa Using Photo Identification and Automated Software

Abstract: South Africa is reputed to host the world’s largest remaining population of white sharks, yet no studies have accurately determined a population estimate based on mark-recapture of live individuals. We used dorsal fin photographs (fin IDs) to identify white sharks in Gansbaai, South Africa, from January 2007 – December 2011. We used the computer programme DARWIN to catalogue and match fin IDs of individuals; this is the first study to successfully use the software for white shark identification. The programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
0
43
2
Order By: Relevance
“…This differed from the swimming patterns at Dyer Island and Geyser Rock, where sharks spent the majority of daytime hours at or close to the Geyser Rock system, only moving to other areas at night. This difference may be attributed to varying age-classes, as sharks at Dyer Island and Geyser Rock are predominantly sub-adult to adults that primarily feed on marine mammals (Estrada et al 2006, Ferrara et al 2011, Towner et al 2013. In contrast, sharks at Mossel Bay are predominantly juvenile to sub-adult that feed on teleost, cephalopod and other reef-based prey as well as marine mammals (Estrada et al 2006, Johnson & Kock 2006, Ferrara et al 2011, Smale & Cliff 2012.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This differed from the swimming patterns at Dyer Island and Geyser Rock, where sharks spent the majority of daytime hours at or close to the Geyser Rock system, only moving to other areas at night. This difference may be attributed to varying age-classes, as sharks at Dyer Island and Geyser Rock are predominantly sub-adult to adults that primarily feed on marine mammals (Estrada et al 2006, Ferrara et al 2011, Towner et al 2013. In contrast, sharks at Mossel Bay are predominantly juvenile to sub-adult that feed on teleost, cephalopod and other reef-based prey as well as marine mammals (Estrada et al 2006, Johnson & Kock 2006, Ferrara et al 2011, Smale & Cliff 2012.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sharks at Mossel Bay are predominantly juvenile to sub-adult that feed on teleost, cephalopod and other reef-based prey as well as marine mammals (Estrada et al 2006, Johnson & Kock 2006, Ferrara et al 2011, Smale & Cliff 2012. Interestingly, large sharks are also found inshore of Dyer Island and Geyser Rock, predominantly during summer months (Towner et al 2013) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though Gleiss et al [10] found little effect from the tagging on the second dorsal fin of whale sharks, for white sharks, these biologging tags, which generally range in size from 100 to 500 g, must be placed on the first dorsal fin. These fins are biologically critical for stability while fast swimming [11] and are used scientifically as means to uniquely identify individuals across decades [12] and estimate abundance [13,14]. Additionally, some communities are dependent on white sharks for ecotourism, so there are sensitivities to the risk (or perceived risk) of damage to dorsal fins from attaching data loggers [15].…”
Section: Introductionmentioning
confidence: 99%